Ligand‐Free Suzuki–Miyaura Cross‐Coupling Reactions in Deep Eutectic Solvents: Synthesis of Benzodithiophene Derivatives and Study of their Optical and Electrochemical Performance. Issue 45 (18th August 2020) - Pelliccioli, Valentina; Dilauro, Giuseppe; Grecchi, Sara; Arnaboldi, Serena; Graiff, Claudia; Perna, Filippo M.; Vitale, Paola; Licandro, Emanuela; Aliprandi, Alessandro; Cauteruccio, Silvia; Capriati, Vito
Abstract : We report that dihalogeno‐substituted benzodithiophenes (BDTs ) undergo a smooth ligand‐free Suzuki–Miyaura cross‐coupling reaction, under air and moderate heating (60 °C), with aryl‐, alkenyl‐ and alkynyltrifluoroborate salts in a biodegradable choline chloride‐based eutectic mixture, thereby granting access to valuable π‐conjugated BDT compounds (up to 79 % yield), which are gaining great interest in the field of material sciences. The optical and electrochemical properties of these systems have been thoroughly investigated by means of absorption and cyclic voltammetry measurements. The first electrooligomerization study of a representative BDT derivative has also been undertaken. Abstract : Valuable π‐conjugated benzodithiophene derivatives have been prepared through a ligand‐free Suzuki–Miyaura cross‐coupling reaction, under mild aerobic conditions, in deep eutectic solvents (DESs) as environmentally responsible reaction media, and their optical and electrochemical properties were investigated.